PENGARUH EKOSISTEM DIGITAL TERHADAP KECENDERUNGAN PEREMPUAN PEMILIK UMKM MENGGUNAKAN METODE PEMBAYARAN NON-TUNAI DI KUTA SELATAN - Meydianawathi, Luh Gede; Tisnawati, Ni Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025DO - 10.24843/EEB.2025.v14.i01.p07, 2025)
The transformation of digital technology shown by the rapid progress of the digital ecosystem, has brought many advances in digital technology, especially in the payment system. The ease of transactions by utilizing digital technology, efficiency and safeness are the basic reasons why many people and Micro, Small, Medium Enterprises (MSME) use less-cash payments in running their daily businesses. However, there are still many obstacles in the adoption of this fintech, especially experienced by women MSMEs. This study aims to analyse the influence of the digital ecosystem and other control variables on the tendency of women MSME owners to use non-cash payment methods in South Kuta. Using purposive sampling technique, data and information collection was conducted through interviews with 98 respondents. The analysis method used is binary logistic model regression. The results of this study indicate that a supportive digital ecosystem greatly influences the tendency of women MSME owners in South Kuta to use less-cash payment methods.